A study on HPV mRNA test and colposcopy in HIV positive women for early detection of cervical intraepithelial lesions - Singh, Kavita N.; Achale, Sheetal; Ghanghoriya, Vineeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Sexually transmitted infections (STIs) have a profound impact on sexual and reproductive health worldwide. At any point of time, globally more than 290 million women suffer from HPV infection, one of the most common STIs. There are only few studies from India reported regarding the prevalence of HPV and cervical abnormalities among HIV-positive women. This study was carried out to estimate the prevalence of HPV and other genital tract infection in HIV positive women and correlate HPV mRNA test and colposcopic findings with cyto-histopathology in HIV positive women who are not on antiretroviral therapy (ART). Secondary objective was to benefit HIV positive women by making them aware about the importance of screening, early detection and treatment of various lower genital tract infections, CIN and cancer cervix. Methods: cross sectional observational study was conducted in department of Obstetrics and Gynecology, NSCB medical college Jabalpur (M.P.) from March 2015 to August 2016 on 70 HIV positive women in whom anti-retroviral therapy was not started. This study was approved by institutional ethical committee. The data was recorded in predesign coded case report form and statistical analysis was performed using the STATA 12.1. Results: In the present study, prevalence of lower genital tract infections in HIV positive women not on ART was 30.0% and the prevalence of high risk HPV was 5.9%. Conclusions: The study concludes that diagnostic efficacy of HPV mRNA test has similar diagnostic value as that of histopathology report.